2018
DOI: 10.1039/c7ra12522d
|View full text |Cite
|
Sign up to set email alerts
|

N-doped carbon dots from phenol derivatives for excellent colour rendering WLEDs

Abstract: Yellow-green photoluminescence carbon dots with different quantum yields were realized and used to fabricate white LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…For the N 1s peak, the peak was deconvoluted into three sub-peaks at 397.9 eV, 399.7 eV, and 400.9 eV, which were assigned for pyridinic, amine, and pyrrolic N, respectively, as shown in Figure 2c. The deconvoluted N 1s peak had a good agreement with the N functional groups that exist on PAR and chitosan [101].…”
Section: Xps Characterization Of Thin Filmsmentioning
confidence: 58%
See 1 more Smart Citation
“…For the N 1s peak, the peak was deconvoluted into three sub-peaks at 397.9 eV, 399.7 eV, and 400.9 eV, which were assigned for pyridinic, amine, and pyrrolic N, respectively, as shown in Figure 2c. The deconvoluted N 1s peak had a good agreement with the N functional groups that exist on PAR and chitosan [101].…”
Section: Xps Characterization Of Thin Filmsmentioning
confidence: 58%
“…The O 1s spectra for the gold/GO thin film were deconvoluted into two sub-peaks at 530.9 eV and 532.9 eV that were assigned to C=O and C–O or C–O–C bonds, respectively. For the N 1s peak, the peak was deconvoluted into three sub-peaks at 397.9 eV, 399.7 eV, and 400.9 eV, which were assigned for pyridinic, amine, and pyrrolic N, respectively, as shown in Figure 2 c. The deconvoluted N 1s peak had a good agreement with the N functional groups that exist on PAR and chitosan [ 101 ].…”
Section: Resultsmentioning
confidence: 97%
“…The absorption spectrum of the CNDs showed the typical -* transition band at 250-275 nm [26] while in the N-doped CNDs a shoulder at 350 nm is typically assigned to the n-* transitions of the N centers (Figures 2d-2e) [1,25,26]. The broad absorption in the visible range has been previously attributed to a wider distribution of N levels and/or the presence of oxygen functional groups present in surface defects [5,16,20,26,31,47,76,85,89,90].…”
Section: Synthesis and Characterization Of Undoped And N-doped Carbonmentioning
confidence: 85%
“…Transmission electron microscopy (TEM) analysis of the collected suspensions showed a narrow size distribution of nanoparticles with mean diameters of 2.3 ± 1.6 nm and 2.0 ± 0.7 nm for the CNDs derived from toluene ( Figure S1 and Figure S2a) and pyridine (Figure 1a and Figure S2b), respectively. HR-TEM revealed that both CNDs are highly crystalline (Figure 1a-1b and Figure S1a-S1b) stacked in a hexagonal crystal structure corresponding to graphite 2H with a space group P6_3mc [84,85]. These structures were confirmed on multiple individual CNDs by FFT images that rendered lattice distances of 0.184 nm, 0.199 nm and 0.210 nm corresponding to (102), (101) and (100) planes of graphite 2H (see Figure 1c and Figure S1), respectively [84,85].…”
Section: Synthesis and Characterization Of Undoped And N-doped Carbonmentioning
confidence: 99%
See 1 more Smart Citation